Cylindrical Dielectric Resonator Optical Antenna (CDROA) & its Applications for Convenient Technology - Mohan, Anand (International Journal of Computer Sciences and Engineering, 2019)
The unique and special features of Dielectric Resonator Antenna (DRA) which has mainly focus on good quality communication with low profile Antenna. Cylindrical Dielectric Resonator optical Antenna (CDROA) is compact in structure, light in weight conformable to surface planar some natural carbon atom form hollow cylinder with out side diameter of only one nano meter. Dielectric Resonator Antenna is well suited for microwave devices integration and feeding Technique and, especially with the microwave integrated circuit technology. In addition, technological applications for such as direct broadcast Technique for satellite system on satellite communication at global positioning system (GPS) and high frequency navigation system and good accuracy and a large variety of radar systems demand for good quality Antenna for the best performance of antenna system.